The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41427-019-0186-y
|View full text |Cite
|
Sign up to set email alerts
|

Artificially engineered nanostrain in FeSexTe1-x superconductor thin films for supercurrent enhancement

Abstract: Although nanoscale deformation, such as nanostrain in iron chalcogenide FST) thin films, has attracted attention owing to the enhancement of general superconducting properties, including critical current density (Jc) and critical transition temperature, its formation has proven to be an extremely challenging and complex process thus far. Herein, we successfully fabricated an epitaxial FST thin film with uniformly distributed nanostrain by injection of a trace amount of CeO2 inside FST matrix using sequenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
(102 reference statements)
0
10
0
Order By: Relevance
“…Since the discovery of superconductivity in LaFeAsO in 2008, iron-based superconductors (IBS) have attracted widespread attention due to their unique properties compared with both traditional low-temperature and high- T c cuprate superconductors. Among all the IBS, FeSeTe, known as the “11”-family IBS, has the advantages of simple structure, nontoxicity (without As), high current-carrying density, and low anisotropy, making it have great potential for high-field applications. The critical transition temperature ( T c ) of a bulk FeSeTe superconductor is relatively low compared with the other family of IBS. It has been found, from the FeSe x Te 1– x phase diagram, that the optimal doping is observed at x = 0.5 with the maximum T c of 15 K .…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of superconductivity in LaFeAsO in 2008, iron-based superconductors (IBS) have attracted widespread attention due to their unique properties compared with both traditional low-temperature and high- T c cuprate superconductors. Among all the IBS, FeSeTe, known as the “11”-family IBS, has the advantages of simple structure, nontoxicity (without As), high current-carrying density, and low anisotropy, making it have great potential for high-field applications. The critical transition temperature ( T c ) of a bulk FeSeTe superconductor is relatively low compared with the other family of IBS. It has been found, from the FeSe x Te 1– x phase diagram, that the optimal doping is observed at x = 0.5 with the maximum T c of 15 K .…”
Section: Introductionmentioning
confidence: 99%
“…Selenium has been a point of focus in materials research over the past few decades, owing to its high photoconductivity and use for the synthesis of a wealth of chemicals. Particularly interesting are metal selenides, which find applications in thermoelectrics, semiconductor quantum dots, photovoltaics, magnetic semiconductors, and superconductors. The ubiquitous applications of selenide materials prompt the need to develop facile, simple, and nontoxic means of synthesis. The conventional syntheses of transition metal selenides usually involve solid-state reactions of elements and precursors, chemical vapor deposition, and gas phase reactions. , These reactions require high temperatures, which are energy intensive and may restrict the control of products.…”
Section: Introductionmentioning
confidence: 99%
“…Trialkylphosphine selenides have also been used as precursors to synthesize high-quality transition metal selenide nanocrystals. It has been demonstrated that the phosphine route may be suitable for materials where surface passivation is required to minimize surface recombination sites; however, for materials with applications in photovoltaics and sensors, the presence of bulky surface-bound organic species may impede device performance. , Furthermore, the reaction of Se with alkyl phosphines such as trioctylphosphine (TOP) and tributylphosphine (TBP) results in unstable and hazardous products, which are difficult to control even under inert atmospheres. This led to the adoption of phosphine-free precursors, which are formed by dissolving Se in high-boiling-point solvents such as oleylamine, octadecene, olive oil, and paraffin. It has been demonstrated that these phosphine-free selenium precursors are more reactive toward particle growth when compared to their phosphine counterparts. , Unfortunately, this strategy is usually associated with the formation of H 2 Se, which acts as a major deactivation pathway during precursor formation and also poses health concerns . Another strategy involves the use of selenourea and elemental Se under a reductive atmosphere (NaBH 4 , hydrazine, concentrated NaOH/KOH), alkyl thiol reduction, and reaction of SeO 2 in coordinative solvents. ,, Most of the aforementioned reducing agents are unstable in air, and their mechanisms of action are complicated .…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal chalcogenides display astounding properties ranging from electronic, thermal, optical properties to novel forms of superconductivity and magnetism. Among various prominent transition-metal chalcogenides, silver-based ones are comparatively less well-explored in the literature. Among them, silver selenide (Ag 2 Se) is an n-type chalcogenide with a phase transition at atmospheric pressure from semiconducting orthorhombic to superionic cubic where Ag + becomes mobile within a rigid lattice of Se.…”
Section: Introductionmentioning
confidence: 99%